Effects of supplemental degradable intake protein on intake and digestibility of bermuda hay - C.P. Mathis; R.C. Cochran; J.S. Heldt; B.C. Woods; Gerald L. Stokka; K. C. Olson; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1998)
A study with 16 ruminally fistulated beef steers fed Bermuda hay ad libitum showed that the intake and digestibility of hay was not influenced by increasing levels of supplemental degradable intake protein (DIP). However, the hay used in this study was of medium quality; lower quality Bermuda hay with lower CP may respond to supplemental DIP.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Steers; Forage; Intake; Digestion; Degradable intake protein